2013
DOI: 10.4161/epi.27474
|View full text |Cite
|
Sign up to set email alerts
|

RevSex duplication-induced and sex-related differences in theSOX9regulatory region chromatin landscape in human fibroblasts

Abstract: It was recently shown that duplications of the RevSex element, located 0.5 Mb upstream of SOX9, cause XX-disorder of sex development (DSD), and that deletions cause XY-DSD. To explore how a 148 kb RevSex duplication could have turned on gonadal SOX9 expression in the absence of SRY in an XX-male, we examined the chromatin landscape in primary skin fibroblast cultures from the index, his RevSex duplication-carrier father and six controls. The ENCODE project supports the notion that chromatin state maps show ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…In their scenario, the addition of a third copy causes local chromatin alteration, allowing this third copy to escape the repressive ‘female’ chromatin environment and to adopt a permissive ‘male’ chromatin state, resulting in activation of putative testis-specific enhancers within the RevSex/XXSR region, leading to upregulation of SOX9 . In support of this, a recent study reported that the RevSex duplication in a 46,XX DSD individual was associated with a more open chromatin signature as also observed in male but not female controls 34. However, as this study was performed on primary fibroblasts, it may not reflect the state of early gonadal Sertoli or granulosa cells.…”
Section: Discussionmentioning
confidence: 72%
“…In their scenario, the addition of a third copy causes local chromatin alteration, allowing this third copy to escape the repressive ‘female’ chromatin environment and to adopt a permissive ‘male’ chromatin state, resulting in activation of putative testis-specific enhancers within the RevSex/XXSR region, leading to upregulation of SOX9 . In support of this, a recent study reported that the RevSex duplication in a 46,XX DSD individual was associated with a more open chromatin signature as also observed in male but not female controls 34. However, as this study was performed on primary fibroblasts, it may not reflect the state of early gonadal Sertoli or granulosa cells.…”
Section: Discussionmentioning
confidence: 72%
“…As hypothesized by Lybaek and colleagues, the RevSex element may interact with other known regulatory elements of SOX9 such as the TESCO motif or the minimal promoter region of SOX9 . In a study of a familial case of XX sex‐reversal carrying a 148 kb RevSex duplication, the chromatin landscape at the TESCO enhancer element was found to be modified in cells from XX masculinized individuals [Lybæk et al, ]. The authors speculate that the RevSex duplication was acting to induce long‐range epigenetic changes including a more open chromatin landscape at the TESCO element resulting in the upregulation of SOX9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether our data reinforce the role of the desert region upstream of SOX9 in the regulation of this gene, as indicated by an altered histone methylation signature demonstrated in one of the RevSex duplicated cases. 40 It is noteworthy that RevSex includes two lncRNAs, TCONS_00025195 and TCONS_00025196, with specific expression in the testis, 41 possibly having a role in SOX9 transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%